Caracterização bioquímica e biológica da peçonha e hemolinfa de Tityus paraguayensis - Henrique Ranieri Covali Pontes (2022)
Scorpions are arthropods from the order Scorpiones, with approximately 2654 species described and distributed in the different ecosystems, many of which are endemic. These animals have hemolymph and venom glands, which can be inoculated into the prey by the telson. Therefore, scorpions are venomous animals, although about 50 species are of medical importance. Both the hemolymph and the venom have components with different biochemical and biological functions, including some of pharmacological and/or biotechnological interest. Therefore, the present study aimed to characterize biochemically and biologically the venom and hemolymph of the scorpion endemic to Mato Grosso do Sul, Tityus paraguayensis. For this purpose, the following steps were carried out: electrophoretic assay; proteolytic, phospholipasic, lipolytic and antitryptic activities; analysis of antitrypanosomal activity; assessment of cytotoxicity; the effect of venom and hemolymph on the (Na+,K+)-ATPase activity; and chromatographic assays. It was observed that the venom has a great diversity of components, as well was detected proteolytic, phospholipasic and lipolytic activity In addition, the venom increased the activity of the enzyme (Na+,K+)-ATPase and decreased the viability of epimastigote forms of T. cruzi. No cytotoxicity against normal cells and antitryptic activity were observed to Tityus paraguayensis venom. The hemolymph showed low protein diversity, but it was seen the proteolytic and lipolytic activities. The results demonstrate that the Tityus paraguayensis venom and hemolymph have potential for bioprospecting for compounds of pharmacological and/or biotechnological interest, requiring further studies to characterize and isolate these components.